Youth desistance in transition : navigating change in late adolescence / Christopher Kay. - Kay, Christopher (International series on desistance and rehabilitation., 2026)
'Youth Desistance in Transition' offers a new and innovative way of thinking about desistance from crime, fusing our understanding of desistance transitions, youth transitions, and the impact of significant policy change on people with convictions in a way which is yet to be seen in the available desistance literature.